From school to fitting work: How education-to-job matching of European school leavers is related to educational system characteristics. (November 2014) - Levels, Mark; van der Velden, Rolf; Di Stasio, Valentina
Although optimal labour market allocation of school leavers benefits individuals, employers and societies, a substantial part of European school leavers do not find a job that matches their field or level of education. This paper explores the extent to which horizontal and vertical education-to-job matches of European school leavers from secondary education is associated with the level of stratification, standardization, and the level of vocational orientation and institutional linkages of education systems. We combine notions of signalling theory, human capital theory and job matching theory to formulate hypotheses about how education systems affect horizontal and vertical education-to-job matches. We use micro-data on 30, 805 school leavers in 20 European countries from the 2009 Ad Hoc Module of the European Labour Force Survey and data on system characteristics. Using multi-level logistic regression, we show that the level of stratification of secondary education is associated with better vertical job matches. We also find that the positive relation between being vocationally trained and education-to-job matches is stronger in systems with stronger institutional linkages. The positive relation between being vocationally trained and vertical job matches is less strong in more vocational oriented systems. Theoretical and practical implications are discussed.